Jaringan Kereta Api sebagai Sarana Transportasi Pendukung Industri Perkebunan di Sumatera Timur: Peranan Deli Maatschappij dan Deli Spoorweg Maatschappij, 1881-1940 - Muhajir, Ahmad; Anwar, Syaiful; Sumantri, Pulung (Warisan: Journal of History and Cultural Heritage, 2020)
This article discusses the history of railways as transportation support for the plantation industry in East Sumatra in the period 1881-1940. The history of railways in East Sumatra can not be separated from the history of Deli tobacco plantations since the beginning of the arrival of Nienhuys, which became the early era of Deli Maatschappij. Deli Maatschappij was the one who built the entire railroad network and all its facilities along the East Sumatra plantation belt area since the 19th century through its subsidiary named Deli Spoorweg Maatschappij (DSM). The method used is the historical method. A literature study conducted is to reconstruct the history of railways in East Sumatra collected from a number of historiographies. The results found that DSM has built a 553,223 km rail network along the plantation area of the east coast of Sumatra. The progress achieved by Deli Maatschappij and DSM can be said as a benchmark for the success of the plantation industry in East Sumatra. The existence of the plantation industry, the presence of private entrepreneurs, and the construction of the railroad network later greatly influenced the development of the city of Medan as a new business center with all the modern urban facilities that complement it.Keywords: transportation history, railways, Deli Spoorweg Maatschappij, East Sumatra plantations.